Peran Transformasi Digital melalui Aplikasi GrabFood terhadap Peningkatan Kinerja Penjualan dan Loyalitas Konsumen Mie Cot - Angelia Salvana Sagita; Seila Elvina Febriani; Laily Muzdalifah (LPPM Universitas KH. A. Wahab Hasbullah, 2026)
Digital transformation is a tactic that can strengthen the competitiveness of small, medium, and micro enterprises, particularly in the culinary sector. However, the use of digital marketing platforms still faces several challenges in its implementation. This community service program aims to assist the Mie Cot MSME in maximizing the use of the GrabFood platform as a digital marketing tool to expand its market reach. The methods implemented include a participatory, action-based approach that follows the steps of needs identification, outreach and education, technical training, intensive support, and evaluation and follow-up. The findings from this activity indicate that partners are able to activate and utilize the GrabFood platform effectively, registering seven menu items digitally with additional photos, prices, and product descriptions, and obtaining initial transactions through the platform. Furthermore, partners also experienced increased knowledge of digital marketing management and online-based promotional strategies. However, implementation challenges remain, including suboptimal product visibility and a lack of significant increases in turnover and customer numbers during the mentoring period. Therefore, ongoing promotion optimization and evaluation are necessary to ensure the use of digital platforms can deliver better results in business development.